Oral health indices predict individualised recall interval - Haukka, Anna (Clin Exp Dent Res, 2020)
OBJECTIVES: The individualised recall interval (IRI) is part of the oral health examination. This observational, register‐based study aimed to explore how oral health indices DMFT (decayed, missing, filled teeth), DT (decayed teeth), CPI (Community Periodontal Index, maximum value of individual was used) and number of teeth are associated with IRI for adults. METHODS: Oral health examination includes an assessment of all oral tissues, diagnosis, a treatment plan and assessment and a determination of the interval before the next assessment. It is called the IRI. This cross‐sectional study population included 42,533 adults (age range 18–89 years), who had visited for an oral health examination during 2009, provided by the Helsinki City Social Services and Health Care. The recall interval was categorised into an ordinal scale (0–12, 13–24, 25–36 and 37–60 months) and was modelled using a proportional odds model. ORs less than one indicated a shorter recall interval. RESULTS: Recall interval categories in the study population were 0–12 months (n = 4,569; 11%), 13–24 months (n = 23,732; 56%), 25–36 months (n = 12,049; 28%), and 37–60 months (n = 2,183; 5%). The results of statistical models clearly showed an association between the length of recall intervals and oral health indices. In all models, higher values of DMFT, DT and CPI indicated a shorter recall interval. The number of teeth were not so relevant. The association was not influenced when different combinations of other predictors (age, gender, socioeconomic status, chronic diseases) were included in the model. The severity of periodontitis predicted a short recall interval, for example, in the Model 1, CPI maximum value 4 was OR = 0.35 (95% confidence interval 0.31–0.40). CONCLUSIONS: The oral health indices showed a clear association with the length of the IRI. Poor oral health reduced IRI. The indices provide information about the amount of oral health prevention required and are useful to health organisations.